Harmonization of IFRS and AAOIFI Standards in Islamic Banking Accounting: Systematic Synthesis and Bibliometric Mapping - Havna, Havna; Maulana, Muhammad; Saktia Fitri, Rati; Muliadi, Muliadi; Yunizar, Muhammad; Zainuri, Hamzah (Syarah: Jurnal Hukum Islam dan Ekonomi, 2025)
This study examines the challenges of harmonizing IFRS-based reporting and AAOIFI standards in Islamic banking accounting. The study uses a Systematic Literature Review (SLR) based on PRISMA 2020 of 25 indexed journal articles from 2020 to 2025, supplemented by a co-occurrence bibliometric analysis using VOSviewer to map dominant themes. The synthesis results show that there are major tensions in the application of IFRS 9 based on expected credit loss (ECL) for Islamic contracts, the need for cross-country comparability, and the role of Shariah governance in maintaining reporting integrity. Stronger compliance with AAOIFI and SSB oversight tends to be associated with higher reporting conservatism and lower indications of earnings management, while IFRS adoption increases comparability but has the potential to obscure the risk-sharing character if contract disclosures are limited. This study proposes a hybrid reporting approach: IFRS as the primary report, supplemented by AAOIFI disclosures and maqasid-based information to enhance transparency, accountability, and value relevance. Operational recommendations are provided for regulators, standard setters, auditors, and Islamic banks.